Non-conventional options of managing municipal solid waste towards sustainable solid waste management in Makassar City - S Towolioe; A S Permana; H Kadang (My University, 2020)
Abstract The traditional approach of handling municipal solid waste in many cities in Indonesia has led to the failure in certain degree of the solid waste management (SWM). On the other hand, the non-conventional options are the approaches to transform this business-as-usual approach to sustainable SWM that aims at accomplishing the appropriate proportion of the elements in waste hierarchy towards sustainable solid waste management. This study aims at assessing the present non-conventional approaches in municipal solid waste management undertaken by waste authorities in Makassar City. We conducted an in-depth investigation and interview with the actors/members, users, citizens and authorities on current status of non-conventional options of SWM. Four hundred and two respondents have been acquired their opinion and perception. Analysis on their perceptions was done by using 5-point Likert scale, by expecting to represent the respondents’ voices in carrying out the SWM activities. From the study, we confirmed that activities towards sustainable solid waste management are not always cost-intensive activities, a socially-bounded engagement, as reflected in by community in the study area, would also workable. We affirm that a livable city will not be accomplished without sustainable solid waste management.
Keywords: solid waste management; Waste Management and Recycling